2020
DOI: 10.1097/pas.0000000000001507
|View full text |Cite
|
Sign up to set email alerts
|

SOX6 is a Novel Immunohistochemical Marker for Differential Diagnosis of Epithelioid Mesothelioma From Lung Adenocarcinoma

Abstract: The differential diagnosis of epithelioid mesothelioma from lung adenocarcinoma using immunohistochemistry is improving. However, immunohistochemical markers with high sensitivity and specificity have yet to be identified. In this study, we investigated the utility of sex-determining region Y box 6 (SOX6) as a novel immunohistochemical marker, identified by analyzing previous gene expression data. Immunohistochemically, SOX6 expression was present in 53 of 54 (98%) cases of epithelioid mesothelioma, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…SOX6 is a newly described immunohistochemical biomarker of mesothelial differentiation and is reportedly highly sensitive and specific for pleural mesothelioma when lung adenocarcinoma is in the differential diagnosis. 13 In this study, we characterized SOX6 expression in peritoneal mesothelial lesions and tuboovarian serous tumors, with 2 principal conclusions:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SOX6 is a newly described immunohistochemical biomarker of mesothelial differentiation and is reportedly highly sensitive and specific for pleural mesothelioma when lung adenocarcinoma is in the differential diagnosis. 13 In this study, we characterized SOX6 expression in peritoneal mesothelial lesions and tuboovarian serous tumors, with 2 principal conclusions:…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also in keeping with a prior report on SOX6 expression in pleural MM, in which the authors found SOX6 expression in an ovarian carcinoma metastatic to the lung. 13 Published data on SOX6 expression in tubo-ovarian serous tumors are limited. One study of 26 ovarian HGSC and endometrioid carcinoma found that SOX6 protein was significantly less abundant in tumor tissue than in non-neoplastic ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] SRY-box transcription factor 6 (SOX6), a HMG-box transcription factor, is underexpressed in the majority of human cancers, such as Ewing sarcoma, leukemia, and lung adenocarcinoma. [27][28][29] Functional studies in ESCC cell lines indicate that SOX6 has anticancer activity in ESCC. [30][31][32][33] Here, our findings support the suppressive activity of circ_0001946 in ESCC cell malignant phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…SRY‐box transcription factor 6 (SOX6), a HMG‐box transcription factor, is underexpressed in the majority of human cancers, such as Ewing sarcoma, leukemia, and lung adenocarcinoma 27–29 . Functional studies in ESCC cell lines indicate that SOX6 has anticancer activity in ESCC 30–33 .…”
Section: Introductionmentioning
confidence: 99%